La testimonianza fra memoria e storia. In che consiste la verità dello sterminio? - Moroncini, Bruno (Bollettino Filosofico, 2016)
According to historian Pierre Nora a victimage paradigm has become increasingly important in contemporary historiography and has transformed the historical science into a courtroom. Laws punishing the crime of Negationism with prison in many countries provide evidence of this process of judicialization of history. In order to testify to the existence of the Holocaust against historical revisionism, this essay examines the need to reject the thesis that historical judgements are constative utterances and supports the thesis that they are performative utterances instead. In other words, the essay shows that truth is an ethical issue, a categorical imperative.